Influence of Fe tablets to Increase Hemoglobin Levels of TB Patients in District of Seberang Ulu I Palembang City: Pengaruh Pemberian Tablet Fe Terhadap Peningkatan Kadar Hemoglobin Pasien TB di Kecamatan Seberang Ulu I Kota Palembang - Novita, Emma; pariyana, Pariyana (Sriwijaya Journal of Medicine, 2018)
People with active pulmonary TB are often macronutrient deficiencies, weight loss and decreased appetite. TB patients are susceptible to anemia, with Fe tablets given is able to cure low TB hemoglobin levels. The method of this study was conducted with the design of Quasi Experimental study. The population was tuberculosis patients in Seberang Ulu I District, with 25 sample of positive TB patients. Samples were given Fe tablet for 90 days. The results of this study were given Fe tablet tablets that affected significant hemoglobin levels (P <0.002) between patients before was before and after tablets were given. The increment of hemoglobin levels of patients before and after the end of tablet given of TB patients was 1.16 g / dl. Suggestions that can be given is the need to be given Fe tablets in TB patients to improve nutritional status so that treatment can achieve optimal results.